Clinical prognostic relevance of elastin and laminin in children with undifferentiated connective tissue disease - N.S. Cherkasov; T.N. Doronina; A.V. Prakhov; Yu.A. Lutsenko (LCC «Medicine-Inform», 2021)
N.S. Cherkasov1, T.N. Doronina1, A.V. Prakhov2, Yu.A. Lutsenko3 1Astrakhan State Medical University, Astrakhan, Russian Federation 2Privolzhsky Research Medical University, Nizhny Novgorod, Russian Federation 3Children's City Polyclinics No. 150, Moscow, Russian Federation; Aim: to determine clinical prognostic relevance of elastin and laminin in children with undifferentiated connective tissue disease (UCTD). Patients and Methods: 47 children with UCTD aged 3-6 were enrolled. The diagnosis was verified by ruling out genetic disorders via analyzing family tree, genetic consultation, etc. Phenotypic and visceral signs were interpreted based on "Congenital and multifactorial connective tissue diseases in children" guidelines (2016). The results of cardiovascular and urinary tract ultrasound were analyzed. Serum levels of elastin and laminin were measured by the sandwich ELISA using high-sensitive kits. All tests were performed at admission and after two years. Results: prognostic relevance (prognostic coefficient) of individual phenotypic and visceral signs and lab tests and prognostic threshold value (the sum of prognostic coefficients indicating high, moderate, or low risk of UCTD progression) were determined. It was demonstrat ed that measuring elastin and laminin levels improves the efficacy of UCTD progression risk assessment. This phenomenon was supported by the values of their prognostic coefficient, which were comparable to the values of significant phenotypic and visceral signs. Furthermore, the accuracy of prognosis based on the use of a set of prognostic indicators (phenotypic, visceral, and biochemical) was supported by the escalation of dysplasia signs. After two years, disease progression was reported in 36 out of 38 children with a moderate and high risk of UCTD progression as identified by the initial evaluation. Conclusion: given the relevance of elastin and laminin in dysplasia pathogenesis, these parameters are considered informative to assess the risk of dysplasia progression in children aged 3-6. It is reasonable to use elastin and laminin levels as additional criteria to evaluate the risk of UCTD progression. Keywords: undifferentiated connective tissue disease, prediction, c hildren, phenotypic signs, laminin, elastin, risk of progression, cardiovascular system, urinary system. For citation: Cherkasov N.S., Doronina T.N., Prakhov A.V., Lutsenko Yu.A. Clinical prognostic relevance of elastin and laminin in children with undifferentiated connective tissue disease. Russian Journal of Woman and Child Health. 2021;4(4):351-354 (in Russ.). DOI: 10.32364/2618-8430-2021-4-4-351-354.